What Constitutes a Local Public Sphere? Building a Monitoring Framework for Comparative Analysis - Fischer, Renate (2021)
Despite the research tradition in analyzing public communication, local public spheres have been rather neglected by communication science, although they are crucial for social cohesion and democracy. Existing empirical studies about local public spheres are mostly case studies which implicitly assume that cities are alike. Based on a participatory-liberal understanding of democracy, we develop a theoretical framework, from which we derive a monitor covering structural, social, and spatial aspects of local communication to empirically compare local public spheres along four dimensions: (1) information, (2) participation, (3) inclusion, and (4) diversity. In a pilot study, we then apply our monitor to four German cities that are comparable in size and regional function (‘regiopolises’). The monitoring framework is built on local statistical data, some of which was provided by the cities, while some came from our own research. We show that the social structures and the normative assessment of the quality of local public spheres can vary among similar cities and between the four dimensions. We hope the innovative monitor prototype enables scholars and local actors to compare local public spheres across spaces, places, and time, and to investigate the impact of social change and digitalization on local public spheres.